Genome‐wide DNA methylation patterns associated with sleep and mental health in children: a population‐based study. (3rd May 2020) - Koopman‐Verhoeff, Maria Elisabeth; Mulder, Rosa H.; Saletin, Jared M.; Reiss, Irwin; van der Horst, Gijsbertus T.J.; Felix, Janine F.; Carskadon, Mary A.; Tiemeier, Henning; Cecil, Charlotte A.M.
Abstract : Background: DNA methylation (DNAm) has been implicated in the biology of sleep. Yet, how DNAm patterns across the genome relate to different sleep outcomes, and whether these associations overlap with mental health is currently unknown. Here, we investigated associations of DNAm with sleep and mental health in a pediatric population. Methods: This cross‐sectional study included 465 10‐year‐old children (51.3% female) from the Generation R Study . Genome‐wide DNAm levels were measured using the Illumina 450K array (peripheral blood). Sleep problems were assessed from self‐report and mental health outcomes from maternal questionnaires. Wrist actigraphy was used in 188 11‐year‐old children to calculate sleep duration and midpoint sleep. Weighted gene co‐expression network analysis was used to identify highly comethylated DNAm 'modules', which were tested for associations with sleep and mental health outcomes. Results: We identified 64 DNAm modules, one of which associated with sleep duration after covariate and multiple testing adjustment. This module included CpG sites spanning 9 genes on chromosome 17, including MAPT – a key regulator of Tau proteins in the brain involved in neuronal function – as well as genes previously implicated in sleep duration. Follow‐up analyses suggested that DNAm variation in this region is under considerable genetic control and shows strong blood–brain concordance. DNAm modules associated with sleep did not overlap with those associated with mental health. Conclusions: We identified one DNAm region associated with sleep duration, including genes previously reported by recent GWAS studies. Further research is warranted to examine the functional role of this region and its longitudinal association with sleep.